Reliable Accessibility of Intermediate Polarization States in Textured Ferroelectric Al0.66Sc0.34N Thin Film - Tae Yoon Lee; Myeong Seop Song; Jung Woo Cho; In Hyeok Choi; Chihwan An; Jong Seok Lee; Seung Chul Chae (Advanced Electronic Materials, 2024)
Abstract Ferroelectric materials are promising candidates for neuromorphic computing synaptic devices due to the nonvolatile multiplicity of spontaneous polarization. To ensure a sufficient memory window, ferroelectric materials with a large coercivity are urgently required for practical applications in highly scaled multi‐bit memory devices. Herein, a remarkable reliability of intermediate ferroelectric polarization states is demonstrated in a textured Al0.66Sc0.34N thin film with a coercive field of 2.4 MV cm−1. Al0.66Sc0.34N thin films are prepared at 300 °C on Pt (111)/Ti/SiO2/Si substrates using a radio frequency reactive sputtering method. Al0.66Sc0.34N thin films exhibit viable ferroelectricity with a large remanent polarization value of >100 µC cm−2. Through the conventional current–voltage characteristics, polarization switching kinetics, and temperature dependence of coercivity, the reproducibility of multiple polarization states with apparent accuracy is attributed to a small critical volume (3.7 × 10−28 m3) and a large activation energy (3.3 × 1027 eV m−3) for nucleation of the ferroelectric domain. This study demonstrates the potential of ferroelectric Al1‐xScxN for synaptic weight elements in neural network hardware.